The professional socialization of the athletic trainer serving as a preceptor - Mazerolle, S. M.; Bowman, T. G.; Dodge, T. M. (Journal of Athletic Training, 2014)
Context: The role of the preceptor requires the athletic trainer to be versed in effective instructional techniques, supervisory skills, and communication skills beyond his or her competence as an athletic trainer, but many have not received formal training in educational techniques. Objective: To gain a better understanding about the professional socialization process for the athletic trainer assuming the role of the preceptor. Design: Qualitative study. Setting: Athletic training education programs. Patients or Other Participants: Twenty-four preceptors (11 men, 13 women; age = 32 ± 7 years, clinical experience = 9 ± 6 years, preceptor experience = 5 ± 3 years) employed in the collegiate (n = 12) or secondary school (n = 12) setting. Data Collection and Analysis: We gathered data using asynchronous, in-depth interviewing via QuestionPro. We analyzed data using a general inductive approach to uncover the dominant themes. Credibility was secured by using consistency and stakeholder checks and a peer review. Results: We identified 2 main themes by which preceptors develop in their roles as clinical instructors: formal processes and informal processes. The participants used observations, previous experiences or interactions with role models, and self-reflection and evaluation as informal socialization processes. Formal socialization processes included preceptor training/workshops, professional development, and formal teacher certification. Conclusions: Athletic trainers who serve as preceptors learned their roles by a combination of informal and formal processes. Preceptor training sessions appeared to be effective in initially helping preceptors learn their responsibilities, whereby more informal processes seemed to help them refine their skills. Furthermore, one socialization strategy did not appear to dominate role learning; rather, a combination of several processes fostered an understanding.